Kemampuan Siswa Pada Materi Aljabar Dengan Realistic Mathematics Education (RME) Berdasarkan Tahapan Berpikir Kritis Facione - Nurkasanah, Hilda Sinta; Suryanti; Sari, Ayu Silvi Lisvian (Papanda, 2025)
In this study, a descriptive qualitative approach was employed, with data collection tools consisting of tests, interviews, and document analysis. The subjects involved were three seventh-grade students from class VII E at SMPN 1 Sanankulon, selected based on test results and recommendations from their mathematics teacher, representing three levels of cognitive ability: high, moderate, and low. After analyzing the collected data, it was found that each student demonstrated potential for critical thinking, with varying levels of achievement influenced by their conceptual understanding and ability to process information. The assessment of critical thinking skills was based on Facione’s four indicators: interpretation, analysis, evaluation, and inference. The findings showed that: (1) Students with high ability were able to solve each problem while clearly addressing all four of Facione’s indicators and applying accurate strategies and calculations. (2) Students with moderate ability did not fully demonstrate all four indicators but showed sufficient computational skills and arrived at correct answers, although they were not thorough in documenting their solution processes. (3) Students with low ability failed to meet all four indicators comprehensively, were less meticulous in presenting their solutions, and made frequent errors in their calculations.